Aplikasi Dukungan Pelajar Pandemi Covid Jakarta - Masya, Fajar; Nugroho, Adi Putro (Universitas Komputer Indonesia, 2020)
The Corona virus has now infected more than 100 countries in the world. WHO has also declared the Corona virus a pandemic. This means that the Corona virus has spread to almost the entire world, including Indonesia. The virus is spread through human interaction from an infected person to another through droplets from the nose or mouth when the infected person coughs, sneezes and even exhales. This condition made the Indonesian government immediately make a decision to break the chain of the spread of COVID-19 by carrying out activities from home including learning system activities in a network or called online as an effort to prevent transmission of the Corona Virus. From the impact of the Covid pandemic, it has a very bad impact on underprivileged students, because there are still many students who do not have facilities for online learning or e-learning. Therefore, the author intends to provide support for students facing the Covid 19 pandemic in facilitating the rental of gadget and laptop equipment as well as individual and collective internet packages for Citizen Homes (RW) at affordable prices and open acceptance of donations gadget or laptop for people who want to help students through based applications. web with the Codeigniter framework, namely